Evaluation of The Implementation of Fe Tablets for Adolescent Girl in 2019 at Pekanbaru City - Fathia Maulida; Asih Setiarini; Endang Laksminingsih Achadi (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2021)
Background: The program for giving Fe tablets is one of the efforts to overcome anemia based on WHO recommendations, one of the targets is the adolescent girl. Indicators of the success of this program are decreasing the incidence of anemia in adolescent girls and increasing adherence to iron tablets consumption. Objectives: This research aims to determine the implementation of the Fe tablets program for adolescent girls in 2019 in Pekanbaru City. Methods: This research uses a qualitative method which is then presented with a descriptive narrative. The data obtained are primary data obtained and collected by in-depth interviews with informants and secondary data by document review and then analyzed by content analysis. Results: The results showed that the implementation of the Fe tablets program for young women in Pekanbaru City has been running, but there are still many obstacles in its implementation so that the scope of success of this program has not reached the national target. Constraints in its implementation include the lack of coordination of cross-sectoral cooperation, the lack of provision of IEC media in socialization, and the low level of compliance of adolescent girls in consuming iron tablets.Conclusions: It is necessary to strengthen coordination and control in the implementation of the Fe tablets program for adolescent girls in Pekanbaru City, it is necessary to increase the procurement of IEC media to support the success of this program and there is a need for improvement providing education to the adolescent girl and even parents or guardians on the knowledge about the importance of this Fe tablets program.Keywords: Fe tablets, adolescent girl, IEC